Promoting the Middle East Peace Process by Changing Beliefs About Group Malleability - Halperin, Eran; Russell, Alexandra G.; Trzesniewski, Kali H.; Gross, James J.; Dweck, Carol S. (Science (American Association for the Advancement of Science), 2011)
Four studies showed that beliefs about whether groups have a malleable versus fixed nature affected intergroup attitudes and willingness to compromise for peace. Using a nationwide sample (N = 500) of Israeli Jews, the first study showed that a belief that groups were malleable predicted positive attitudes toward Palestinians, which in turn predicted willingness to compromise. In the remaining three studies, experimentally inducing malleable versus fixed beliefs about groups among Israeli Jews (N = 76), Palestinian citizens of Israel (N = 59), and Palestinians in the West Bank (N = 53)—without mentioning the adversary—led to more positive attitudes toward the outgroup and, in turn, increased willingness to compromise for peace.